Lipid peroxidation status, somatic mutations and micronuclei in peripheral lymphocytes: a case observation on a possible interrelationship - Mayer, Claudia; Schmezer, Peter; Bartsch, Helmut (Cancer letters, 2000)
A controlled dietary study was conducted in healthy female volunteers and reported elsewhere [1]. In a subset of samples four different biomarkers were analyzed: plasma malondialdehyde (MDA) levels and urinary 8-isoprostaglandin-F2α were measured as markers for lipid peroxidation. The frequency of hprt (hypoxanthine guanine phosphoribosyl transferase) mutants and micronuclei in peripheral blood lymphocytes were analyzed as indicators of genotoxic effects. One of the ten individuals showed extremely high background levels in all of the four endpoints measured. This case observation raises the possibility that life style factors and dietary habits affect the level of DNA reactive lipid peroxidation products, which in turn increase mutagenic and cytogenetic effects. A possible association between these biomarkers, particularly in relation to dietary fat intake and antioxidant status, should now be studied in a larger trial.
Gesehen am 28.01.2021